Perlindungan Hukum bagi Pekerja akibat tidak Adanya Perjanjian Kerja dalam Wedding Organizer - Yehezkiel Cristofer Tambunan; Adhitya Widya Kartika (Yustisia Tirtayasa, 2022)
One industry that has close relationships with customers is the Wedding Organizer (WO) industry. However, it turns out that there are problems that often cause misunderstandings for the Wedding Organizer (WO) in running their business, namely the absence of a written agreement to provide certainty to the Wedding Organizer (WO) workers. This also raises the potential for Default in this business or Wedding Organizer (WO) business. Civil law contains legal regulations that make a person's promise the legal basis. Civil law can be expressed from legal regulations based on someone's promise. There are several laws both in criminal law and constitutional law that include a person's promise as a component, such as the offense of embezzlement through Article 372 in the Indonesian Criminal Code or the Civil Service Act, but these laws are rare in number. . A pledge must be made in good faith so that the parties do not dispute the terms, but in most Wedding Organizers (WO), it is very rare for business actors to make formal agreements, leaving the relationship without any guarantees. legal certainty that occurs between business actors and Wedding Organizer (WO) workers. An employment agreement between employees and employers at Prabu Wedding Organizer (WO) and LM Wedding Organizer (WO) who do not have a working relationship using a written agreement, is an illustration. Based on the characteristics of the research and the legal documents which were obtained during the writing of this research, the following thesis is written using a descriptive analysis method, where the data is analyzed using analytic methods with a qualitative approach to the main data and secondary data. The author uses empirical juridical research in writing further research, especially research that includes sociological law and is usually called field research. the agreement between the worker and the owner of the Wedding Organizer (WO) without a written agreement is still valid and requires the subjects to legally regulate the terms of the engagement and that legal remedies can be carried out by the Wedding Organizer (WO) employees and in the event of default by the employer (employee) ) is none other than by suing the wedding organizer (WO) employer with existing evidence, namely what is clearly contained in Article 1866 of the Civil Law Regulations and Article 64 of the Civil Procedure Code of Regulations